Strategi Pemberdayaan Pembangunan Sosial Melalui Gerakan Filantropi Islam - Ulza, Emaridial; Kurniawan, Herwin (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2018)
This research would like to see the patterns of Social Development Empowerment Through Islamic Philanthropy Movement. The main problem in philanthropy is the lack of proper strategy in implementing Lembaga Amil Zakat (LAZ) and Badan Amil Zakat (BAZ) in Indonesia. In particular the philanthropy movement undertaken by Lazismu does not run evenly in every region. There are only certain Lazismu such as Lazismu Central Java, Lazismu East Java, and Lazismu Yogyakarta. One example of Lazismu Central Java in the month of Ramadan managed to collect money of 37 billion. This figure is a fantasy number that can be collected in just 1 month by this newly established philanthropic institution. The results of this study produce relationships with others. Islamic philanthropy and eminent empowerment strategy became a better philanthropic movement of Islam.